CHEMICAL REACTION EFFECTS ON MHD FREE CONVECTIVE OSCILLATORY FLOW PAST A POROUS PLATE EMBEDDED IN A POROUS MEDIUM IN THE PRESENCE OF RADIATION - Ramana, R. Mohana (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
thingray fluid with electrically conducting incompressible viscous fluid past an infinite vertical porous plate embedded in a porous medium, through which suction occurs with constant velocity. A uniform magnetic field is assumed to be applied transversely to the direction of the free stream taking into account of induced magnetic field. The governing equations involved in the present analysis are solved by using the perturbation method. The velocity, temperature and concentration fields are studied for different parameters such as Grashof number (Gr), modified Grashof number (Gc), Magnetic field parameter (M), Permeability parameter (k), Schmidt number (Sc), Prandtl number (Pr), radiation parameter (S), Chemical reaction parameter (Kr) and Eckert number (Ec) etc. Keywords: MHD, Oscillatory flow, porous medium, Radiation, chemical reaction etc